Implementing Civic Culture to Improve Students' Environmental Awareness at SMPN 1 Bayan - Gustia, Mila; Zubair, Muh.; Alqadri, Bagdawansyah; Basariah, Basariah (Universitas Islam Negeri Sumatera Utara, 2025)
This study examines the implementation of civic culture in improving students' environmental awareness at SMPN 1 Bayan, North Lombok, as a response to the low awareness of cleanliness and discipline in waste management. Descriptive qualitative method was used involving 6 students, 2 teachers, and 1 principal as subjects. Data were collected through interviews, observations, and documentation, then analyzed thematically. The results showed that the integration of civic culture (knowledge, skills, and attitudes of citizenship) through the